Copyrighting God: Ownership of the Sacred in American Religion - Clifford B. Anderson (Theological Librarianship, 2021)
This is a review of Andrew Ventimiglia. Copyrighting God: Ownership of the Sacred in American Religion. Cambridge: Cambridge University Press, 2019), vii + 247pp. $115 hardcover; $34.99 softcover. ISBN: 9781108420518 (hardcover); 9781108430371 (softcover).